EFFECT OF WATER IMMERSION TEMPERATURE ON HEART RATE VARIABILITY FOLLOWING EXERCISE IN THE HEAT (Kinesiology, 2018)
This study compared the effect of passive rest (CON) and water immersion at 8.6±0.2°C (CWI9), 14.6±0.3°C (CWI15) and 35.0±0.4°C (thermoneutral water immersion [TWI]) on post-exercise heart rate variability (HRV) indices. In a climate chamber (32.8±0.4°C, 32±5% relative humidity), nine men completed 25 min of cycling at the first ventilatory threshold and repeated 30-second bouts at 90% of peak power followed by a 5-minute recovery treatment in a randomised crossover manner. All water immersion re-established the HRV indices (natural logarithm of the square root of the mean sum squared differences between RR intervals [ln rMSSD], low-frequency [lnLF] and high-frequency power densities [lnHF] and Poincaré plotderived measures [lnSD1 and lnSD2]) to the pre-exercise levels at 60 min post-immersion; however, only CWI9 accelerated parasympathetic reactivation during immersion. CWI9 increased lnLF and lnSD2 during immersion when compared with CON (p0.80) on all HRV indices during immersion when compared with CON, between-conditions differences were observed only in lnLF and lnSD2 (p=.017-.023). CWI15 had a large positive ES on ln rMSSD and lnSD1 when compared with CON (both p=.064). Sympathovagal antagonism (i.e., SD ratio